Preparation and Characterization of Nanohybrid Antioxidant from Propyl Gallate and Evaluation of its Antioxidant Activity - Abeer Muhammedali Alnasrawi (Journal of Global Pharma Technology, 2018)
In this study a nanohybrid antioxidant Mg/Al-PG-LDH was prepared by intercalating propyl gallate (PG) between magnesium/ aluminum layered double hydroxides. Identification of the prepared compound by the FT-IR revealed that some functional groups had been shifted either to higher or lower frequencies indicating the preparation of new compound. X-ray diffraction analysis confirmed the crystalline   nature of the prepared compound. The antioxidant activity of the nanohybrid compound was evaluated using three methods. In the ABTS cation radical scavenging assay the IC50 of PG and Mg/Al-PG-LDH were (50 and 100) µg/ml, respectively. By using ferric reducing antioxidant power (FRAP), analysis of the results allowed to rank the antioxidants used in this study as follows: Mg/Al-PG-LDH < Trolox< PG. The standard antioxidant butylated hydroxyl anisole exhibited the highest chelating effect in compare with the nanohybrid antioxidant and PG.Keywords: Propyl gallate, Nanohybrid antioxidant, FT-IR, XRD, ABTS, FRAP, and Chelating effect